Comparing the Geographic Distributions and Growth of Mormons, Adventists, and Witnesses. - Lawson, Ronald; Cragun, Ryan T. (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2012)
Mormons, Adventists, and Witnesses have all felt called to take their teachings to the world and have experienced growth. However, they have varied considerably in both their geographic spread-where they have developed a presence over time-and also in where they have been more successful numerically. The result is sharply differing profiles: Adventists are concentrated more in the developing world; Witnesses and Mormons are proportionately stronger in the developed world, but in different parts of it. Within countries, Witnesses and Mormons are more urban, while Adventists are more concentrated in rural regions; Adventists also tend to be poorer than Witnesses and especially practicing Mormons. The article explores why these differing patterns developed, expanding on a recently developed theoretical model by Cragun and Lawson that religious growth depends on the synchronization of supply and demand and their corresponding components.